Examining entrepreneurial intentions in adult population in China and Pakistan: GEM data evidence - Raheem Bux Soomro; Yuan Honglin (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
This research manuscript is aimed at to examine entrepreneurial intentions through the cognitive approach of Chinese and Pakistani adults. Data for this research was acquired from the database of GEM 2012 APS Global Individual Level. The entrepreneurial intention was a dependent variable while independent variables were individual perceptions, socio-cultural perceptions and perceptions of economic opportunities. Their effect on intentions is tested along with some control variables. Four logistic regressions were employed to test three hypotheses. Fear of failure was not found as a significant predictor of entrepreneurial intentions in both countries. Gender is also not a significant predictor of entrepreneurial intentions in China. But it is significant in Pakistan; therefore, we can say that males are more likely to hold entrepreneurial intentions in Pakistan. The results of role model, self-efficacy and perception of economic opportunities are positive and significant predictors of entrepreneurial intentions in both countries. From socio-cultural perceptions, status and respect and news in media have been found strong predictors of entrepreneurial intentions among Chinese adults while career choice and news in media have been found strong predictors of entrepreneurial intentions among Pakistani adults. Pakistani government should encourage Small and Medium Enterprise Development Authority to provide basic entrepreneurial training (Entrepreneurial Idea Generation) to adults and commercial and micro-finance banks/institutes to lend small and big loans to adults who prefer to open their firms/businesses.
Keywords: 330; entrepreneurial intention; fear of failure; knowledge of other entrepreneurs; perception of capabilities; perception of opportunities and global entrepreneurship monitor (GEM)